EU COHESION POLICY REFORM OF 2004–2006: CHALLENGES AND RESULTS - Trakelis, Darius (Politologija, 2015)
In this article I analysed one of the goals of the 2004–2006 Cohesion policy reform – to adjust the Cohesion policy to the new reality: increased development disparities in the Union after Enlargement. I argue that despite big changes caused by Enlargement the Commission with its reform proposal of 2004 in principle did not try to reform anything. Cohesion policy priorities, which were proposed by the Commission for the period of 2007–2013 as well as distribution of financing among them, were left similar to ones of 2004–2006 period, while decision on Cohesion policy reform taken by the European Council in the end of 2005, which finalised two years of Member States discussions, just slightly improved the situation.The Cohesion policy reform of 2004–2006 actually did not reform this policy, because increased development disparities in the EU were overshadowed by indirect factor of Enlargement – its costs to the Member States of the EU-15. Rich Member States or “net-payers” to the EU budget, one third of which is traditionally allocated for Cohesion policy, were concerned about increase of their contributions as a consequence of Enlargement to 12 less developed Member States. While southern Member States, which during the period of 2000–2006 were main beneficiaries of Cohesion policy, tried to maintain substantial amount of structural assistance, though after Enlargement they lost the status of least developed Member States in the Union.Reacting to the challenges of Enlargement and trying “not to harm” main Cohesion policy beneficiaries of 2000–2006 period the Commission simply increased the Cohesion policy budget by about 100 billion euro without any big changes in the Policy’s priorities or their financial proportions. The analysis of the Commission proposal showed that, contrary to the declared reform goal – to adjust Cohesion Policy to the increased development disparities in the Union after Enlargement, – practically the Commission’s aim was to neutralise the costs of Enlargement to the Member States of the EU-15: was foreseen a transitional support for the regions, which level of development artificially increased due to the “statistical effect” caused by Enlargement and the assistance allocation method (so called “Berlin method”) was modified in order to increase assistance to the Member States of the EU-15. In addition, the Commission actively argued in favour of maintaining the so called “4 percent capping rule” (annual structural assistance to any Member State can not exceed 4 percent of its GDP). This resulted in inadequate aid intensity – annual per capita allocations for less developed Member States and regions often were lower than for more prosperous ones.During two years of intensive negotiations the new Cohesion policy priorities proposed by the Commission did not change, changed just amounts of resources allocated for their implementation. Negotiations were not about adjustment of the Cohesion policy to the new reality, but about “money”. Every Member State first of all was concerned about net balance of its payments to and gains from the EU budget. “Net-payers” were not interested in financing the “inflated” Policy foreseeing generous support for all the Member States. Southern Member States, which during entire history of the Cohesion Policy used to receive solid EU structural assistance, expected the same in the financial perspective of 2007–2013. While new Member States argued that in terms of aid intensity per capita they should not receive less than more prosperous Member States.Final agreement, compared with the initial Commission proposal, reduced the resources for the Cohesion Policy by 33 billion euros. Reduction was made more at the expense of the Member States of the EU-15, for them the assistance was reduced by 21 million euro, while new Member States suffered at lesser extent – for them support diminished by 12 billion euro. It should be noted that due to the review of statistics in April 2005, on the basis of which assistance allocations for Member States were calculated, for some new Member States, first of all Baltic States and Slovakia, support increased so substantially, that even after final reduction they received much more structural assistance than it was foreseen for them in the initial Commission proposal.Review of statistical data and higher reduction of assistance allocated to the Member States of the EU-15 than to the new ones decreased the disparities in aid intensity between less developed and more prosperous Member States, though still in many cases allocations of support are inadequate to Member States’ levels of development. Least developed Member States – Bulgaria and Romania – will receive less structural assistance per capita during 2007–2013 than less developed regions in Germany or United Kingdom, while level of support foreseen for Poland, Latvia, Lithuania and Slovakia just slightly exceeds assistance allocated for much more prosperous Member States such as Portugal, Greece and Spain.